Withanolide D Exhibits Similar Cytostatic Effect in Drug-Resistant and Drug-Sensitive Multiple Myeloma Cells - Issa, Mark E.; Wijeratne, E. M. K.; Gunatilaka, A. A. L.; Cuendet, Muriel (Frontiers in Pharmacology, 2017)
In spite of recent therapeutic advances, multiple myeloma (MM) remains a malignancy with very low curability. This has been partly attributed to the existence of a drug-resistant subpopulation known as cancer stem cells (CSCs). MM-CSCs are equipped with the necessary tools that render them highly resistant to virtually all conventional therapies. In this study, the growth inhibitory effects of withanolide D (WND), a steroidal lactone isolated from Withania somnifera, on drug-sensitive tumoral plasma cells and drug-resistant MM cells have been investigated. In MTT/XTT assays, WND exhibited similar cytostatic effects between drug-resistant and drug-sensitive cell lines in the nM range. WND also induced cell death and apoptosis in MM-CSCs and RPMI 8226 cells (RPMIs), as examined by the calcein/ethidium homodimer and annexin V/propidium iodide stainings, respectively. To determine whether P-glycoprotein (P-gp) efflux affected the cytostatic activity of WND, P-gp was inhibited with verapamil and results indicated that the WND cytostatic effect in MM-CSCs was independent of P-gp efflux. Furthermore, WND did not increase the accumulation of the fluorescent P-gp substrate rhodamine 123 in MM-CSCs, suggesting that WND may not inhibit P-gp at the tested relevant doses. Therefore, the WND-induced cytostatic effect may be independent of P-gp efflux. These findings warrant further investigation of WND in MM-CSC animal models.